2006
DOI: 10.1590/s1677-55382006000300005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pelvicaliceal anatomical variation between the stone-bearing and normal contralateral kidney on stone formation in adult patients with lower caliceal stones

Abstract: Objective: We aimed to investigate the effect of pelvicaliceal anatomical differences on the etiology of lower caliceal stones. Materials and Methods: Records of adult patients between January 1996 and December 2005 with solitary lower caliceal stone were reviewed. After exclusion of patients with hydronephrosis, major renal anatomic anomalies, non-calcium stones, history of recurrent stone disease and previous renal surgery, 78 patients were enrolled into the study. Lower pole infundibulopelvic angle (IPA), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Since early hydronephrosis expresses itself morphologically with the presence of an ampullar pelvis in humans, it has been postulated that before labelling this feature as an anatomical variant in the clinical scenario, one must rule out an urinary tract obstruction generated by lithiasis, stenosis of the pyeloureteral junction, vesicoureteral reflux, or extrinsic compression caused by light adhesions of the lower polar renal arteries or the gonadal vessels [6,35]. Similarly, it has been postulated that since bifurcated renal pelvises handle smaller urinary volumes, they could become an anatomical substrate for the formation of stones inside these structures [1,18].…”
Section: Discussionmentioning
confidence: 99%
“…Since early hydronephrosis expresses itself morphologically with the presence of an ampullar pelvis in humans, it has been postulated that before labelling this feature as an anatomical variant in the clinical scenario, one must rule out an urinary tract obstruction generated by lithiasis, stenosis of the pyeloureteral junction, vesicoureteral reflux, or extrinsic compression caused by light adhesions of the lower polar renal arteries or the gonadal vessels [6,35]. Similarly, it has been postulated that since bifurcated renal pelvises handle smaller urinary volumes, they could become an anatomical substrate for the formation of stones inside these structures [1,18].…”
Section: Discussionmentioning
confidence: 99%
“…In that study IPA constituted a statistically significant risk factor for lower incidence of calyceal stones [12]. Kupeli et al [10] in their analysis of the effect of morphological structure of the inferior calyx on development of nephrolithiasis demonstrated absence of any significant correlations between the IPA of the lower pole and formation of stones. Besides morphology of the inferior calyx, structure of the whole renal collective system was analysed in that study.…”
Section: Resultsmentioning
confidence: 86%
“…In our study none of the infundibular factors were significantly different between the affected and unaffected kidney. Kupeli et al [10] reported statistically significant differences in lower calyceal IW (p = 0.001) between the stone-bearing kidney and the contralateral kidney, although there were no differences in lower calyceal IL (p = 0.568). Similarly to IPA, IW is a significant factor affecting the post-ESWL stone-free.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In study conducted by Kupeli Bora et al 3 pelvicalyceal anatomy will be of immense value to the clinicians of related specialties.…”
Section: Infundibular Width (Uiw)mentioning
confidence: 99%